Staying safe online / by Ben Hubbard - Hubbard, Ben, 1973- (Chicago, Illinois : Capstone, 2017)
Presents information about how to remain safe from potentially dangerous situations online.
Includes index
Keywords: Internet and children -- Juvenile literature; Internet -- Security measures -- Juvenile literature; Online etiquette -- Juvenile literature